Computational fluid dynamic analysis in infrarenal abdominal aortic aneurysm for surveillance of aneurysm potential rupture - Nyityasmono Tri Nugroho, MD, PhD; Agus Prasetyo Nuryadi, BEng; Muhammad Ilyas, MD; Muhammad Hanif Nadhif, BEng; Reyhan Eddy Yunus, MD; Raden Suhartono, MD, PhD (JVS-Vascular Insights)
Objective: This study aims to identify the morphology of infrarenal abdominal aortic aneurysms (AAAs) and analyze wall shear stress (WSS) and wall pressure (WP) using computational fluid dynamic analysis to predict potential rupture areas. Methods: A cross-sectional study was conducted on patients with infrarenal AAAs at the Vascular and Endovascular Division, Department of Surgery, and the Department of Radiology, RSUPN Dr Cipto Mangunkusumo, from July to December 2022. Three-dimensional models were reconstructed from computed tomography angiograms, and infrarenal AAAs were classified into five morphologic types. Computational fluid dynamic analysis was performed to generate WSS and WP contours at varying blood pressure and velocity. Visual results for each type were analyzed and compared. Statistical analysis was conducted using SPSS 25.0. Results: From 93 computed tomography angiograms, 40 samples met the inclusion criteria. Twenty-five percent of samples had a saccular component. Visual analysis showed a correlation between areas of lowest WSS and highest WP. Velocity and blood pressure also affected WSS and WP; however, the center of the contour as potential prediction rupture sites remained consistent. Significant differences were found in WSS and WP (P = .038 and P < .001, respectively). Conclusions: Areas of lowest WSS correspond with highest WP, indicating potential rupture sites. Blood velocity and pressure changes also influenced WSS and WP. Surveillance should be subjected to closer inspection on the areas with the lowest WSS.